Expression, crystallization and preliminary X-ray analysis of the extracellular Ig modules I–IV and F3 modules I–III of the neural cell-adhesion molecule L1 - Kulahin, Nikolaj (International Union of Crystallography, 2005)
Four amino-terminal immunoglobulin (Ig) modules and three fibronectin type III (F3) modules of the mouse neural cell-adhesion molecule L1 have been expressed in Drosophila S2 cells. The Ig modules I–IV of L1 crystallized in a trigonal space group, with unit-cell parameters a = b = 239.6, c = 99.3 Å, and the crystals diffracted X-rays to a resolution of about 3.5 Å. The F3 modules I–III of L1 crystallized in a tetragonal space group, with unit-cell parameters a = b = 80.1, c = 131 Å, and the crystals diffracted X-rays to 2.8 Å resolution. This is a step towards the structure determination of the multimodular constructs of the neural cell-adhesion molecule L1 in order to understand the function of L1 on a structural basis.